The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1021/bi049833i
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Posttranslational Modifications of the High Mobility Group A1a Proteins in Breast Cancer Cells of Differing Metastatic Potential

Abstract: The high mobility group (HMG) proteins are important modulators of chromatin structure and gene transcription. Overexpression of HMGA1 proteins in vivo induces neoplastic transformation and promotes a highly metastatic cellular phenotype. This study focuses on characterization of HMGA1a in vivo posttranslational modification (PTM) patterns found in a nonmetastatic and two metastatic lines of MCF-7 human breast cancer cells of differing tumorigenic potential. PTM types and the amino acids on which they occur we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
46
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 49 publications
2
46
1
1
Order By: Relevance
“…Arg 25 , localized within the first AT-hook of HMGA1a, has been shown to be a major site of modification in tumor cells (11), but other Arg residues, in addition to those reported in this paper, have been found methylated in vivo (9,10). In this study, we were unable to identify other PRMTs, except PRMT6, that modify HMGA1a protein.…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations
“…Arg 25 , localized within the first AT-hook of HMGA1a, has been shown to be a major site of modification in tumor cells (11), but other Arg residues, in addition to those reported in this paper, have been found methylated in vivo (9,10). In this study, we were unable to identify other PRMTs, except PRMT6, that modify HMGA1a protein.…”
Section: Discussioncontrasting
confidence: 54%
“…More recently, dimethylation on the same Arg 25 residue has been reported by another group (21). An extensive study on both HMGA1a and HMGA1b proteins reported a high level of PTMs, and in particular, dimethylation of arginine and lysine residues was increased in breast cancer cells with higher metastatic potential (9,10). Altogether, these data lead authors to suggest the existence of a PTM "code" for HMGA proteins similar to that reported for histones (10,11).…”
mentioning
confidence: 52%
See 2 more Smart Citations
“…Reversible acetylation of Lys-64 and Lys-70 modulates the transcription of IFN-␤ gene by regulating the destabilization and formation, respectively, of an enhanceosome on the promoter region of the°IFN-␤°gene° [26,°27].°Lys-64°and°Lys-70°in°HMGA1a were found to be acetylated in nonmetastatic and moderately metastatic breast cancer cells such as MCF-7/Tet-off cells and HA7C cells, but not in highly metastatic°HA8A°breast°cancer°cells° [19].°In°addition,°Lys-14 in HMGA1 proteins was observed to be acetylated in PC-3° [28]°and°HA7C°cells° [19],°whereas°the°same residue was monomethylated in HMGA1a in nonmetastatic MCF-7/Tet-off cells. The biological implications of the acetylation of these lysine residues remain to be established.…”
Section: Discussionmentioning
confidence: 99%